High Nasal Carriage Rate of Staphylococcus aureus Containing Panton-Valentine leukocidin- and EDIN-Encoding Genes in Community and Hospital Settings in Burkina Faso - Ouedraogo, Abdoul-Salam; Dunyach-Remy, Catherine; Kissou, Aimée; Sanou, Soufiane; Poda, Armel; Kyelem, Carole G.; Solassol, Jérôme; Bañuls, Anne-Laure; Van De Perre, Philippe; Ouédraogo, Rasmata; Jean-Pierre, Hélène; Lavigne, Jean-Philippe; et al. (Frontiers in microbiology, 2016)
The objectives of the present study were to investigate the rate of S.aureus nasal carriage and molecular characteristics in hospital and community settings in Bobo Dioulasso, Burkina Faso. Nasal samples (n = 219) were collected from 116 healthy volunteers and 103 hospitalized patients in July and August 2014. Samples were first screened using CHROMagar Staph aureus chromogenic agar plates, and S. aureus strains were identified by mass spectrometry. Antibiotic susceptibility was tested using the disk diffusion method on Müller-Hinton agar. All S. aureus isolates were genotyped using DNA microarray. Overall, the rate of S. aureus nasal carriage was 32.9% (72/219) with 29% in healthy volunteers and 37% in hospital patients. Among the S. aureus isolates, only four methicillin-resistant S. aureus (MRSA) strains were identified and all in hospital patients (3.9%). The 72 S. aureus isolates from nasal samples belonged to 16 different clonal complexes, particularly to CC 152-MSSA (22 clones) and CC1-MSSA (nine clones). Two clones were significantly associated with community settings: CC1-MSSA and CC45-MSSA. The MRSA strains belonged to the ST88-MRSA-IV or the CC8-MRSA-V complex. A very high prevalence of toxinogenic strains 52.2% (36/69), containing Panton-Valentine leucocidin- and EDIN-encoding genes, was identified among the S. aureus isolates in community and hospital settings. This study provides the first characterization of S. aureus clones and their genetic characteristics in Burkina Faso. Altogether, it highlights the low prevalence of antimicrobial resistance, high diversity of methicillin-sensitive S. aureus clones and high frequency of toxinogenic S. aureus strains.